2018
DOI: 10.1534/g3.118.200075
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association and Genomic Selection for Resistance to Amoebic Gill Disease in Atlantic Salmon

Abstract: Amoebic gill disease (AGD) is one of the largest threats to salmon aquaculture, causing serious economic and animal welfare burden. Treatments can be expensive and environmentally damaging, hence the need for alternative strategies. Breeding for disease resistance can contribute to prevention and control of AGD, providing long-term cumulative benefits in selected stocks. The use of genomic selection can expedite selection for disease resistance due to improved accuracy compared to pedigree-based approaches. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 49 publications
(63 reference statements)
11
114
2
Order By: Relevance
“…The prediction accuracy values ranged from 0.678 to 0.758 for GBLUP (with SNP densities ranging from 500 to 18K), while PBLUP only reached an accuracy of 0.637. This result has been mirrored in other studies of genomic versus pedigree-based prediction of disease resistance breeding values for other important farmed fish species, e.g Atlantic salmon (Tsai et al 2015; Yoshida et al 2017; Ødegård et al 2014; Robledo et al 2018), rainbow trout (Vallejo et al 2017; Yoshida et al 2018), sea bream (Palaiokostas et al 2016) and sea bass (Palaiokostas et al 2018a). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al 2016) and Pacific oyster (Gutierrez et al 2018b).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The prediction accuracy values ranged from 0.678 to 0.758 for GBLUP (with SNP densities ranging from 500 to 18K), while PBLUP only reached an accuracy of 0.637. This result has been mirrored in other studies of genomic versus pedigree-based prediction of disease resistance breeding values for other important farmed fish species, e.g Atlantic salmon (Tsai et al 2015; Yoshida et al 2017; Ødegård et al 2014; Robledo et al 2018), rainbow trout (Vallejo et al 2017; Yoshida et al 2018), sea bream (Palaiokostas et al 2016) and sea bass (Palaiokostas et al 2018a). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al 2016) and Pacific oyster (Gutierrez et al 2018b).…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, a high density linkage map containing ∼20K SNPs has recently been created and aligned with the physical reference genome assembly (Gutierrez et al 2018a; Zhang et al 2012). Using such arrays, several studies have demonstrated that genomic selection for aquaculture species results in improved accuracy compared to traditional pedigree-based approaches; for example in Atlantic salmon (Robledo et al 2018), coho salmon (Barría et al 2018), rainbow trout (Vallejo et al 2018), common carp (Palaiokostas et al 2018b), and Pacific oyster (Gutierrez et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…This result has been mirrored in other studies of genomic vs. pedigree‐based prediction of disease resistance breeding values for other important farmed fish species, e.g. Atlantic salmon (Ødegård et al ; Tsai et al ; Yoshida et al ; Robledo et al ), rainbow trout (Vallejo et al ; Yoshida et al ), sea bream (Palaiokostas et al ) and sea bass (Palaiokostas et al ). Further, in shellfish similar findings have been observed for prediction of breeding values for growth traits in scallop (Dou et al ) and Pacific oyster (Gutierrez et al ).…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, a high-density linkage map containing 20 000 SNPs has recently been created and aligned with the physical reference genome assembly (Zhang et al 2012;Gutierrez et al 2018a). Using such arrays, several studies have demonstrated that genomic selection for aquaculture species results in improved accuracy compared with traditional pedigree-based approaches; for example in Atlantic salmon (Robledo et al 2018), coho salmon (Barr ıa et al 2018), rainbow trout (Vallejo et al 2018), common carp (Palaiokostas et al 2018b) and Pacific oyster (Gutierrez et al 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Genomic prediction models were applied using datasets of varying SNP density using either 157 MAF or linkage disequilibrium (LD) values as thresholds for filtering. In particular, to obtain 158 the reduced density SNP panels for genomic prediction, a strategy of retaining SNPs surpassing 159 a sequentially increased MAF threshold was applied, as described in Robledo et al (2018). Four different scenarios were tested for evaluating the impact of genetic relationships between 178 training and validation sets.…”
Section: Prediction Metrics For Khvd Resistance 142mentioning
confidence: 99%